Manajemen Perencanaan Peningkatan Mutu Pendidikan - Sulistio, Didit; Murniati, Ngurah Ayu Nyoman; Miyono, Noor (Universitas Muria Kudus, 2022)
The purpose of this study is to analyze and describe how management planning improves the quality of education at MI Al Mustajab Pringapus. This research uses a qualitative approach with this type of case study research. Research data collection techniques are: (1) observation, (2) in-depth interviews, and (3) documentation. To check the validity of the data, credibility tests are used in the form of source triangulation, triangulation methods and reference materials. The data analysis techniques used are: (1) data reduction (data reduction), (2) data presentation (data display), and (3) conclusion drawing (conclusion drawing image). The results showed that learning planning in the form of: (1) making a management plan to improve the quality of education at MI Al Mustajab Pringapus well would result in better quality education, this is proven by the improvement of madrasah accreditation, academic and non-academic achievements from madrasahs, and also enthusiastic of people abaut madrasah is increase.Â Artikel ini dapat diakses secara terbuka dibawah lisensi CC-BY-SA